Battery cell and method for producing the same, battery device, electric device, energy storage device

CN123017869APending Publication Date: 2026-10-30JINKO SOLAR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611339267.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种电池单体及其制备方法、电池装置、用电装置、储能装置,以解决现有技术中正极片中溶剂残留高且难以兼顾提升正极片粘结力的问题

Benefits of technology

[0020]应用本发明的技术方案,本申请的正极浆料中添加具有上述化学结构通式的添加剂,能够使正极片具有低NMP残留和高粘结强度的优点。具体地,PVDF分子链中含有大量的-CF2-链段,上述种类的添加剂中的氟碳链部分也含有类似的-CF2-结构。由于氟原子具有极高的电负性,C-F键形成强极性键,使得氟碳链之间产生强烈的偶极-偶极相互作用。这种氟-氟相互作用的结合能约为-15至-27kJ/mol,作用距离为0.3~0.6nm,足以在正极浆料中形成稳定的分子级缔合,但又不足以在烘烤时阻碍添加剂的挥发。这种氟-氟相互作用在正极浆料中起到分子模板的作用,能够引导PVDF分子链向活性物质-集流体界面迁移。在烘烤过程中添加剂挥发后,PVDF保持诱导形成的有利取向,形成更强的粘结网络,从而使极片剥离强度提升40~70%。添加剂含有酯基挥发端,使其具有低沸点(<165℃)特性,在烘烤的初期优先挥发,形成连通孔隙通道,从而降低NMP逸出阻力,进而实现在烘烤工艺参数不变的前提下,使NMP残留量降低30~50%,即使降低粘结剂的用量且提高活性物质的用量,也能够使极片的剥离强度提升40~70%。此外,添加剂能够实现无残留,同时在不改变极片原有配方的基础上,进一步提升活性物质的质量占比,从而提升电芯的能量密度。综上,本申请的采用较低含量的添加剂也能够降低正极片的溶剂的残留量,同时提高极片的剥离强度,从而提高电池的能量密度和循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017869A_ABST
    Figure CN123017869A_ABST
Patent Text Reader

Abstract

This invention provides a battery cell, its preparation method, a battery device, an electrical device, and an energy storage device. The battery cell includes a positive electrode, a separator, and a negative electrode. The positive electrode is prepared from a positive electrode slurry, which includes a positive electrode active material, a conductive agent, a binder, additives, and a solvent. The additives have the following general chemical formula: [Formula omitted]. R1 and R2 are each independently substituted or unsubstituted C1~C [Formula omitted]. 18 Alkyl groups; and at least one of R1 and R2 is C1~C2. 18 The additives contain fluoroalkyl groups. The fluorocarbon chains in the additives interact with the binder via fluorine-fluorine interactions, inducing the binder to oriented alignment and thus improving the adhesion of the electrode. During the initial baking stage, the additives preferentially volatilize, forming interconnected pore channels and reducing solvent escape resistance, thereby lowering solvent residue. The additives pose no residue risk and can also increase the mass ratio of active material, thereby improving the energy density of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a battery cell and its preparation method, a battery device, an electrical device, and an energy storage device. Background Technology

[0002] The manufacturing of electrode sheets is crucial to the performance of lithium-ion batteries, and the coating and baking process is a core step in ensuring electrode quality. Positive electrode sheets typically use polyvinylidene fluoride (PVDF) as a binder and N-methylpyrrolidone (NMP) as a solvent to prepare the slurry. During the coating and baking process, the NMP solvent needs to completely evaporate. However, in actual production, the coated electrode sheets are placed in an oven and baked at 120-140°C. The NMP solvent gradually evaporates from the surface of the electrode sheet inwards. Due to the high boiling point of NMP (202°C), the evaporation rate is slow at these baking temperatures. Simultaneously, the electrode surface dries rapidly in the early stages of baking, forming a dense layer that hinders the escape of internal solvent, resulting in a high residual amount of NMP. To address the NMP residue, methods such as increasing the coating and baking temperature to 140-160°C and extending the baking time are commonly used. However, these methods have drawbacks, including increased energy consumption, PVDF aging and electrode embrittlement, reduced production efficiency, high equipment modification costs, and increased electrode cracking.

[0003] Furthermore, the PVDF binder is randomly distributed in the slurry without a specific orientation. During the coating and baking process, the PVDF molecular chains solidify as the solvent evaporates, forming a predominantly amorphous α-phase crystalline structure. In this structure, the bonding between PVDF and the active material mainly relies on van der Waals forces, resulting in limited interfacial bonding strength. To address insufficient adhesion, methods such as increasing the PVDF dosage, using modified PVDF, or adding bonding promoters are commonly employed. However, these methods suffer from increased costs leading to reduced energy density, poor process compatibility, and the potential introduction of impurities that could affect cell performance. Summary of the Invention

[0004] The main objective of this invention is to provide a battery cell and its preparation method, battery device, power supply device, and energy storage device, in order to solve the problems of high solvent residue in the positive electrode sheet and difficulty in improving the adhesion of the positive electrode sheet in the prior art.

[0005] To achieve the above objectives, according to one aspect of the present invention, a battery cell is provided, comprising a positive electrode, a separator, and a negative electrode. The positive electrode is prepared from a positive electrode slurry, which includes a positive electrode active material, a conductive agent, a binder, an additive, and a solvent; the additive has the following general chemical structural formula: Where R1 and R2 are each independently substituted or unsubstituted C1~C1. 18 Alkyl groups; and at least one of R1 and R2 is C1~C2. 18Fluorinated alkyl groups.

[0006] Furthermore, R1 and R2 are each independently substituted or unsubstituted C1~C 12 Alkyl group; at least one of R1 and R2 is C1~C2. 12 The fluoroalkyl group, and the total number of fluorine atoms in R1 and R2 is 1 to 20.

[0007] Furthermore, the additive is selected from any one or more of methyl perfluorooctanoate, ethyl perfluorobutyrate, ethyl 2,2-difluoropropionate, methyl fluoroacetate and ethyl fluoroacetate; and / or, on a dry basis of the positive electrode slurry, the mass percentage of the additive is 0.3 to 0.5%.

[0008] Furthermore, the binder includes polyvinylidene fluoride (PVDF) with a number average molecular weight of 400,000 Da to 600,000 Da.

[0009] Furthermore, the mass ratio of additives to binders is (0.15~0.3):1.

[0010] Furthermore, the solvent includes N-methylpyrrolidone, and the solid content of the positive electrode slurry is 60-66%.

[0011] Furthermore, the positive electrode active material is selected from any one or more of lithium iron phosphate materials, lithium manganese iron phosphate materials, lithium nickel cobalt manganese oxide materials, lithium cobalt oxide, lithium manganese oxide and lithium-rich manganese-based materials; and / or, the conductive agent is selected from any one or more of conductive carbon black, carbon nanotubes, graphene, natural graphite and artificial graphite; and / or, the mass ratio of positive electrode active material, conductive agent, binder and additive is (96~97.5):(0.8~1.2):(1.6~2):(0.3~0.5).

[0012] According to another aspect of the present invention, a method for preparing a battery cell is provided, comprising preparing a positive electrode sheet by sequentially stacking and assembling a positive electrode sheet, a separator, and a negative electrode sheet to obtain a battery cell. The method for preparing the positive electrode sheet includes: mixing raw materials comprising a positive electrode active material, a conductive agent, a binder, an additive, and a solvent to obtain a positive electrode slurry; coating the positive electrode slurry onto the surface of a positive electrode current collector and then drying it to form a positive electrode active layer, thereby obtaining a positive electrode sheet; wherein the general chemical formula of the additive is... Where R1 and R2 are each independently substituted or unsubstituted C1~C1. 18 Alkyl groups; and at least one of R1 and R2 is C1~C2. 18 Fluorinated alkyl groups.

[0013] Furthermore, the method for preparing the positive electrode sheet also includes: first mixing raw materials including positive electrode active material, first conductive agent, binder and additive to obtain a first mixture; second mixing raw materials including the first mixture and first solvent to obtain a second mixture; third mixing raw materials including the second mixture and second solvent to obtain a third mixture; and fourth mixing raw materials including the third mixture and second conductive agent to obtain a positive electrode slurry.

[0014] Further, the temperature of the first mixing is 23~27℃, the revolution speed of the first mixing is 15~25 rpm, and the time of the first mixing is 30~45 min; and / or, the fourth mixing method is dispersion; the revolution speed of the fourth mixing is 20~30 rpm, the dispersion speed of the fourth mixing is 1500~2500 rpm, and the time of the fourth mixing is 60~75 min; and / or, the mass ratio of the first conductive agent and the second conductive agent is 1~2:1; the first conductive agent is selected from any one or more of conductive carbon black, natural graphite, and artificial graphite; the second conductive agent is carbon nanotubes and / or graphene.

[0015] Furthermore, the second mixing method is kneading, the second mixing speed is 20~30 rpm, and the second mixing time is 60~75 min; and / or, the third mixing method is dispersion, the third mixing speed is 20~30 rpm, the third mixing dispersion speed is 1500~2500 rpm, and the third mixing time is 90~120 min; and / or, the mass of the first solvent is 80~90% of the total mass of the first solvent and the second solvent.

[0016] Furthermore, the drying temperature is 120~130℃; and / or, the bifacial areal density of the positive electrode is 400~430 g / m³. 2 .

[0017] According to another aspect of the present invention, a battery device is provided, the battery device comprising the above-described battery cell, and the battery device comprising any one or more of a battery module, a battery pack, and an energy storage battery.

[0018] According to another aspect of the present invention, an electrical device is provided, which includes the battery device described above, the battery device being used to provide electrical energy.

[0019] According to another aspect of the present invention, an energy storage device is provided, which includes the battery device described above, the battery device being used to store electrical energy.

[0020] By applying the technical solution of this invention, the addition of additives with the above-mentioned general chemical structure formula to the positive electrode slurry of this application enables the positive electrode sheet to have the advantages of low NMP residue and high bonding strength. Specifically, the PVDF molecular chain contains a large number of -CF2- segments, and the fluorocarbon chain portion of the above-mentioned additives also contains a similar -CF2- structure. Due to the extremely high electronegativity of fluorine atoms, the CF bonds form strong polar bonds, resulting in strong dipole-dipole interactions between the fluorocarbon chains. The binding energy of this fluorine-fluorine interaction is approximately -15 to -27 kJ / mol, and the interaction distance is 0.3 to 0.6 nm, which is sufficient to form stable molecular-level associations in the positive electrode slurry, but not enough to hinder the volatilization of the additives during baking. This fluorine-fluorine interaction acts as a molecular template in the positive electrode slurry, guiding the PVDF molecular chains to migrate towards the active material-current collector interface. After the additives volatilize during baking, the PVDF retains the favorable orientation induced during baking, forming a stronger bonding network, thereby increasing the electrode sheet peel strength by 40 to 70%. The additive contains ester-based volatile groups, giving it a low boiling point (<165℃). It preferentially volatilizes during the initial baking stage, forming interconnected pore channels, thereby reducing NMP escape resistance. This allows for a 30-50% reduction in NMP residue while maintaining consistent baking process parameters. Even with reduced binder and increased active material content, the electrode peel strength can be improved by 40-70%. Furthermore, the additive achieves residue-free operation and further increases the mass ratio of active material without altering the original electrode formulation, thus improving the cell's energy density. In summary, this application utilizes a lower amount of additive to reduce solvent residue in the positive electrode while improving peel strength, thereby enhancing the battery's energy density and cycle life. Attached Figure Description

[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0022] Figure 1 A schematic diagram of the preparation method of the battery cell of this application is shown. Detailed Implementation

[0023] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0024] As analyzed in the background section of this application, residual NMP reacts with the electrolyte, generating gas that causes cell expansion. This also affects the formation of the SEI film, reducing the cell's initial coulombic efficiency and cycle life. Insufficient PVDF adhesion results in lower-than-expected electrode peel strength, potentially causing powder shedding during rolling and slitting processes. Furthermore, there is a possibility of separation between the active material and the current collector in the later stages of cycling, leading to capacity decay in the cell.

[0025] As analyzed above, the existing technology has the problem of high solvent residue in the positive electrode and difficulty in improving the adhesion of the positive electrode. In order to solve the above problems, this application provides a battery cell and its preparation method, battery device, power consumption device and energy storage device.

[0026] In a typical embodiment of this application, a battery cell is provided, comprising a positive electrode, a separator, and a negative electrode. The positive electrode is prepared from a positive electrode slurry, which includes a positive electrode active material, a conductive agent, a binder, additives, and a solvent. The chemical structural formula of the additives is as follows: Where R1 and R2 are each independently substituted or unsubstituted C1~C1. 18 Alkyl groups; and at least one of R1 and R2 is C1~C2. 18 Fluorinated alkyl groups.

[0027] The addition of additives with the aforementioned general chemical structure to the positive electrode slurry of this application enables the positive electrode sheet to possess the advantages of low NMP residue and high bonding strength. Specifically, the PVDF molecular chain contains a large number of -CF2- segments, and the fluorocarbon chain portion of the aforementioned additives also contains a similar -CF2- structure. Due to the extremely high electronegativity of fluorine atoms, the CF bonds form strong polar bonds, resulting in strong dipole-dipole interactions between the fluorocarbon chains. The binding energy of this fluorine-fluorine interaction is approximately -15 to -27 kJ / mol, and the interaction distance is 0.3 to 0.6 nm, which is sufficient to form stable molecular-level associations in the positive electrode slurry, but insufficient to hinder the volatilization of the additives during baking. This fluorine-fluorine interaction acts as a molecular template in the positive electrode slurry, guiding the PVDF molecular chains to migrate towards the active material-current collector interface. After the additives volatilize during baking, the PVDF retains the favorable orientation induced during baking, forming a stronger bonding network, thereby increasing the electrode sheet peel strength by 40 to 70%. The additive contains ester-based volatile groups, giving it a low boiling point (<165℃). It preferentially volatilizes during the initial baking stage, forming interconnected pore channels, thereby reducing NMP escape resistance. This allows for a 30-50% reduction in NMP residue while maintaining consistent baking process parameters. Even with reduced binder and increased active material content, the electrode peel strength can be improved by 40-70%. Furthermore, the additive achieves residue-free operation and further increases the mass ratio of active material without altering the original electrode formulation, thus improving the cell's energy density. In summary, this application utilizes a lower amount of additive to reduce solvent residue in the positive electrode while improving peel strength, thereby enhancing the battery's energy density and cycle life.

[0028] In one embodiment of this application, R1 and R2 are each independently substituted or unsubstituted C1~C 12 Alkyl group; at least one of R1 and R2 is C1~C2. 12 The fluoroalkyl group, and the total number of fluorine atoms in R1 and R2 is 1 to 20.

[0029] The preferred additives, with their preferred molecular chain length and the number of fluorinated alkyl groups within the aforementioned ranges, help reduce the risk of excessive viscosity increase in the cathode slurry due to excessively long molecular chains, while simultaneously reducing NMP volatilization resistance. The fluorinated alkyl groups with the aforementioned carbon chain lengths both accelerate NMP volatilization and induce the formation of a highly adhesive β-phase in PVDF, thereby further improving the electrode's bonding strength while reducing NMP residue. R1 and R2 can each independently be methyl, ethyl, propyl, -(CF2)6CF3, -(CF2)2CF3, -CF2CH3, or -CH2F. The total number of fluorine atoms in R1 and R2 can be 1, 3, 5, 8, 10, 12, 15, 18, or 20, etc.

[0030] In one embodiment of this application, the additive is selected from any one or more of methyl perfluorooctanoate, ethyl perfluorobutyrate, ethyl 2,2-difluoropropionate, methyl fluoroacetate and ethyl fluoroacetate; and / or, the mass percentage of the additive is 0.3 to 0.5% based on the dry basis of the positive electrode slurry.

[0031] The preferred additives, falling within the aforementioned range, help reduce NMP residue while improving the adhesion strength of the electrode. Methyl perfluorooctanoate (CAS No. 376-27-2), with the chemical formula CF3(CF2)6COOCH3 and a boiling point of 160-165℃, possesses long-chain fluorocarbons that help induce PVDF directional alignment and promote NMP volatilization, enabling the positive electrode to achieve both improved adhesion and low NMP residue. Ethyl perfluorobutyrate (CF3(CF2)2COOCH2CH3), with its short-chain structure, exhibits high volatility and rapid pore formation at low temperatures, helping to reduce baking energy consumption. Ethyl 2,2-difluoropropionate helps improve slurry dispersibility and reduce surface tension. Methyl fluoroacetate has a low boiling point (66℃) and can rapidly evaporate to remove solvent, thereby reducing initial drying energy consumption. Ethyl fluoroacetate, with a boiling point of 84℃, helps achieve solvent removal and improve coating uniformity at a low cost. All of the above additives can be purchased or prepared in-house.

[0032] Taking the principle of methyl perfluorooctanoate promoting NMP volatilization during the coating and baking process as an example:

[0033] During the baking process, the volatilization behavior of methyl fluorooctanoate (PFOA) and NMP exhibits a significant time difference. PFOA has a boiling point of 160–165°C, lower than NMP's 202°C, therefore PFOA volatilizes preferentially in the initial stages of baking. In the temperature range of 60–80°C, PFOA begins to volatilize, forming initial pores; at this point, the volatilization rate of PFOA is approximately 10–30%, while the volatilization rate of NMP is less than 5%. In the temperature range of 80–100°C, a large amount of PFOA volatilizes and forms a porous network, and PVDF begins to align; at this point, the volatilization rate of PFOA is approximately 30–80%, while the volatilization rate of NMP is approximately 5–20%. In the temperature range of 100–120°C, a large amount of NMP volatilizes and escapes through the channels formed by PFOA, while the PVDF network solidifies; at this point, the volatilization rate of PFOA is approximately 80–100%, while the volatilization rate of NMP is approximately 20–70%. Within the temperature range of 120–140°C, NMP can achieve deep removal and electrode shaping, at which point methyl perfluorooctanoate (PFOA) completely volatilizes, and the amount of NMP volatilized is approximately 70–95%. Quantitative analysis shows that without PFOA, the tortuosity of the NMP escape path is approximately 3–5; with PFOA, the tortuosity decreases to 1.5–2.5. According to diffusion theory, the effective diffusion coefficient of NMP is inversely proportional to the tortuosity of the path; therefore, the effective diffusion coefficient of NMP can be increased by approximately 50–100%, thereby reducing the residual amount of NMP.

[0034] Surface energy data for each component indicate that the surface energy of PVDF is 25~30 mJ / m. 2 It exhibits better compatibility with methyl perfluorooctanoate (fluoro-fluoro affinity). The surface energy of lithium iron phosphate active materials is 45~55 mJ / m², and its compatibility with methyl perfluorooctanoate is moderate. The surface energy of conductive agents (conductive carbon black, carbon nanotubes) is 35~45 mJ / m². 2 Its compatibility with methyl perfluorooctanoate is moderate. The surface energy of NMP solvent is 40~42 mJ / m. 2 Its compatibility with methyl perfluorooctanoate is poor. The surface energy of the aluminum foil current collector is 500~600 mJ / m. 2 However, it has poor compatibility with methyl perfluorooctanoate (PFOA). Because PFOA can reduce the surface tension of the slurry, it undergoes positive adsorption at the interface and accumulates at the active material-solvent interface, the conductive agent-solvent interface, and the slurry-air interface. PFOA preferentially adsorbs onto the surface of the active material, forming an active material-PFOA-PVDF structure. This structure forms a pre-bonded network in the slurry, thereby improving the slurry's stability.

[0035] In one embodiment of this application, the adhesive includes polyvinylidene fluoride, the number average molecular weight of which is 400,000 Da to 600,000 Da.

[0036] PVDF exists in multiple crystal forms. The α phase is a thermodynamically stable phase with a TGTG' conformation and a crystallinity of about 40-50%, with a bonding strength at the baseline level. The β phase is a phase with excellent mechanical properties, with a TTTT conformation and highly oriented molecular chains, and a crystallinity of 55-65%. Preferably, the number average molecular weight of PVDF is within the above range. The mass content of the β phase in PVDF is 55-65%, which helps to improve the bonding strength of the electrode by 20-30%.

[0037] The mechanism by which methyl perfluorooctanoate (PFOA) induces the formation of the β phase in PVDF is as follows: 1) The fluorocarbon chains of PFOA are aligned parallel to the PVDF segments, providing a nucleation template. 2) After the ester groups volatilize, they leave ordered spaces, along which the PVDF molecular chains crystallize. 3) The fluorine-fluorine interaction between the two helps to lower the nucleation energy barrier of the β phase, thereby promoting the formation of the β phase. 4) The β phase PVDF has a higher dipole moment and stronger interfacial bonding. Through this crystallization-induced mechanism, the β phase content of PVDF can be increased from 40-50% to 55-65%, while solvent molecules are expelled during crystallization, thereby further improving the bonding strength of the electrode. In one embodiment of this application, the mass ratio of additive to binder is (0.15-0.3):1.

[0038] Optimizing the mass ratio of additives and binders within the above range helps to enhance their synergistic effect, thereby enabling the additives to fully induce the directional alignment of PVDF and construct volatilization channels, thus reducing NMP residue while improving the peel strength of the electrode.

[0039] In one embodiment of this application, the solvent includes N-methylpyrrolidone, and the solid content of the positive electrode slurry is 60-66%.

[0040] Adding N-methylpyrrolidone to the cathode slurry helps disperse the above components, ensuring the solid content of the cathode slurry reaches the aforementioned range, thus facilitating slurry coating. The solid content is calculated as the mass of the solid residue after drying divided by the total mass of the slurry before drying; in other words, the solid content is expressed as a mass percentage.

[0041] In one embodiment of this application, the positive electrode active material is selected from any one or more of lithium iron phosphate materials, lithium manganese iron phosphate materials, lithium nickel cobalt manganese oxide materials, lithium cobalt oxide, lithium manganese oxide and lithium-rich manganese-based materials; and / or, the conductive agent is selected from any one or more of conductive carbon black, carbon nanotubes, graphene, natural graphite and artificial graphite; and / or, the mass ratio of the positive electrode active material, conductive agent, binder and additive is (96~97.5):(0.8~1.2):(1.6~2):(0.3~0.5).

[0042] Preferential selection of the types and mass ratios of positive electrode active materials, conductive agents, binders, and additives within the above-mentioned ranges helps to obtain a positive electrode sheet with "high conductivity network - strong bonding interface - low solvent residue", thereby improving the energy density and cycle life of the battery. Optionally, the conductive agent is conductive carbon black and carbon nanotubes, with a mass ratio of (0.4~0.6):(0.4~0.6).

[0043] In another typical embodiment of this application, a method for preparing a battery cell is provided, including preparing a positive electrode sheet by sequentially stacking and assembling a positive electrode sheet, a separator, and a negative electrode sheet to obtain a battery cell. The method for preparing the positive electrode sheet includes: mixing raw materials comprising a positive electrode active material, a conductive agent, a binder, an additive, and a solvent to obtain a positive electrode slurry; coating the positive electrode slurry onto the surface of a positive electrode current collector and then drying it to form a positive electrode active layer, thereby obtaining the positive electrode sheet; wherein the general chemical formula of the additive is... Where R1 and R2 are each independently C2~C 18 olefinic group, substituted or unsubstituted C1~C 18 Alkyl groups; and at least one of R1 and R2 is C1~C2. 18 Fluorinated alkyl groups.

[0044] The additives in the cathode slurry of this application have low boiling points (<165℃) and preferentially volatilize in the early stages of baking, forming interconnected pore channels. This reduces the resistance to NMP escape, thereby significantly reducing NMP residue while maintaining the baking process parameters. Simultaneously, the fluorocarbon chains in the additives guide the PVDF molecular chains to migrate towards the active material-current collector interface. After the additives volatilize during baking, the PVDF maintains its induced favorable orientation, forming a stronger bonding network and improving the electrode's peel strength. Furthermore, the additives leave no residue after drying, and the mass ratio of active material is further increased without altering the original electrode formulation, thus improving the cell's energy density. In summary, the cathode prepared from the above cathode slurry exhibits low NMP solvent residue and strong peel strength, thereby improving the battery's energy density and cycle life. Moreover, the preparation method of this application allows for mass production of battery cells without altering existing production lines.

[0045] In one embodiment of this application, the method for preparing the positive electrode sheet further includes: when preparing the positive electrode slurry, firstly mixing raw materials including positive electrode active material, first conductive agent, binder and additive to obtain a first mixture; secondly mixing raw materials including the first mixture and first solvent to obtain a second mixture; thirdly mixing raw materials including the second mixture and second solvent to obtain a third mixture; and fourthly mixing raw materials including the third mixture and second conductive agent to obtain the positive electrode slurry.

[0046] In preparing the positive electrode slurry, the positive electrode active material, the first conductive agent, the binder, and the additives are first mixed. This helps the additives to initially disperse and contact the surface of the binder particles in a dry-mixed state, reducing local enrichment or agglomeration of the additives due to surface tension differences during subsequent solvent addition. Adding the solvent in steps helps to fully disperse the above components in the solvent, thereby improving the compositional uniformity of the positive electrode slurry. The second conductive agent (such as carbon nanotubes, CNTs) has a large aspect ratio and is easy to entangle. Adding it in the fourth mixing step, when the slurry matrix (active material + binder) has already formed a stable framework, allows the second conductive agent to achieve uniform dispersion, which is beneficial for forming a conductive network. Therefore, the stepwise mixing method used in the above-mentioned positive electrode slurry preparation helps the additives and binders enter the solvent system together in the second mixing step, allowing the additives to undergo fluorine-fluorine interactions with the PVDF molecular chains to induce alignment, while maintaining a uniform state before subsequent baking.

[0047] In one embodiment of this application, the temperature of the first mixing is 23~27℃, the revolution speed of the first mixing is 15~25 rpm, and the time of the first mixing is 30~45 min; and / or, the fourth mixing method is dispersion; the revolution speed of the fourth mixing is 20~30 rpm, the dispersion speed of the fourth mixing is 1500~2500 rpm, and the time of the fourth mixing is 60~75 min; and / or, the mass ratio of the first conductive agent and the second conductive agent is 1~2:1; the first conductive agent is selected from any one or more of conductive carbon black, natural graphite, and artificial graphite; the second conductive agent is carbon nanotubes and / or graphene.

[0048] Preferably, the temperature, rotation speed, and time of the first mixing are within the above-mentioned ranges, which helps the additives and binders to make sufficient contact, thereby reducing the residual solvent and improving the peel strength of the electrode. Preferably, the method, rotation speed, dispersion speed, and time of the fourth mixing are within the above-mentioned ranges, which helps the second conductive agent to be fully dispersed in the slurry, thereby helping to form a conductive network, thereby reducing the internal resistance of the electrode, while maintaining the rheological stability of the slurry, thus improving the uniformity of coating and the consistency of the electrochemical performance of the electrode. Preferably, the length of the carbon nanotubes is less than 5 μm.

[0049] Definition of revolution speed: refers to the rotational speed at which the mixing pot (or planetary carrier) revolves around the central axis of the equipment.

[0050] Definition of dispersion speed: The rotational speed at which a high-speed dispersion disc (or serrated disc) installed inside a mixing pot rotates around its own axis.

[0051] In one embodiment of this application, the second mixing method is kneading, the second mixing speed is 20-30 rpm, and the second mixing time is 60-75 min; and / or, the third mixing method is dispersion, the third mixing speed is 20-30 rpm, the third mixing dispersion speed is 1500-2500 rpm, and the third mixing time is 90-120 min; and / or, the mass of the first solvent is 80-90% of the total mass of the first solvent and the second solvent.

[0052] Preferably, the second mixing method, revolution speed, and time are within the above-mentioned ranges, which helps to initially disperse the components in a large amount of the first solvent. Pre-selecting the third mixing method, revolution speed, dispersion speed, and time are within the above-mentioned ranges, which helps to utilize the strong shear force generated by high-speed dispersion to reduce the agglomeration of conductive agents and active substances, and allows the system to reach the ideal rheological state after the remaining small amount of solvent is added.

[0053] In one embodiment of this application, the drying temperature is 120~130℃; and / or, the bifacial areal density of the positive electrode is 400~430 g / m³. 2 .

[0054] The preferred drying temperature within the above range helps to preferentially volatilize the additives and form interconnected pores before NMP evaporates in large quantities, thereby reducing the resistance to NMP escape and thus reducing the residual amount of NMP. Simultaneously, it induces PVDF to form a β-phase crystalline structure with high bonding strength, thereby improving the peel strength of the electrode. The preferred bifacial areal density of the positive electrode within the above range helps to maintain the mechanical strength of the electrode while increasing the energy density of the cell.

[0055] In another typical embodiment of this application, a battery device is provided, which includes the above-mentioned battery cell, and the battery device includes any one or more of battery modules, battery packs, and energy storage batteries.

[0056] Battery devices including the aforementioned battery cells have superior overall performance in terms of high power output, wide temperature range operation, and long cycle life, making them suitable for energy storage systems and power battery applications with high requirements for energy density, safety, and reliability.

[0057] In another typical embodiment of this application, an electrical device is provided, which includes the battery device described above, the battery device being used to provide electrical energy.

[0058] The aforementioned battery devices enable electrical devices to have higher energy efficiency, longer service life and more stable power output characteristics, making them suitable for applications such as energy storage systems and electric vehicles with stringent requirements for safety and cycle performance.

[0059] In another typical embodiment of this application, an energy storage device is provided, which includes the battery device described above, the battery device being used to store electrical energy.

[0060] Energy storage devices including the aforementioned battery devices can effectively reduce interface impedance, suppress dendrite growth, and improve the cycle life and rate performance of batteries in a wide temperature range environment. They are suitable for energy storage systems with comprehensive requirements for energy density, safety and low temperature adaptability, and are especially suitable for high-reliability energy storage application scenarios under solid-state battery architecture.

[0061] Furthermore, the battery cell using the aforementioned cathode material of this application can not only maintain high specific capacity but also achieve excellent long-cycle performance, thus making it more suitable for the needs of long-term energy storage systems. This battery cell possesses high volumetric energy density and excellent cycle stability, and can efficiently support the operation of large-scale energy storage power stations at the 4-hour (4h) and 8-hour (8h) levels, meeting the stringent requirements for high-capacity batteries in application scenarios such as grid peak shaving and smooth output of renewable energy.

[0062] The beneficial effects of this application will be further illustrated below with reference to the embodiments.

[0063] Example 1

[0064] Adopting such Figure 1 The method for preparing the positive electrode sheet in the battery cell preparation method shown is as follows:

[0065] The positive electrode active material (lithium iron phosphate), the first conductive agent (conductive carbon black), the binder (PVDF, number average molecular weight of 500,000 Da), the second conductive agent (carbon nanotubes), and the additive (methyl perfluorooctanoate) were prepared according to a mass ratio of 97:0.6:1.8:0.5:0.4.

[0066] Lithium iron phosphate, conductive carbon black, PVDF, and methyl perfluorooctanoate were first mixed in a stirred tank at 25°C, 20 rpm, and for 30 min to obtain a first mixture. Then, 80% (by mass) of NMP solvent was added to the first mixture for a second mixing process using a kneading method at 20 rpm for 60 min to obtain a second mixture. Next, the remaining NMP was added to the second mixture for a third mixing process using a dispersion method at 20 rpm and 1700 rpm for 90 min to obtain a third mixture. Finally, carbon nanotubes were added to the third mixture for a fourth mixing process using a dispersion method at 20 rpm and 1700 rpm for 60 min. The mixture was then passed through a 200-mesh sieve to remove agglomerated particles, yielding a positive electrode slurry with a solid content of 62%.

[0067] The positive electrode slurry was coated on both sides of the positive electrode current collector aluminum foil, with a double-sided areal density of 430 g / m³. 2 The coated electrode is placed in an oven to dry at a temperature of 125°C to form a positive active layer, thus obtaining the positive electrode.

[0068] Example 2

[0069] The difference from Example 1 is that the mass ratio of lithium iron phosphate, conductive carbon black, PVDF, carbon nanotubes and methyl perfluorooctanoate is 97:0.6:1.8:0.5:0.3, and the positive electrode sheet is finally obtained.

[0070] Example 3

[0071] The difference from Example 1 is that the mass ratio of lithium iron phosphate, conductive carbon black, PVDF, carbon nanotubes and methyl perfluorooctanoate is 97:0.6:1.8:0.5:0.5, which ultimately yields the positive electrode sheet.

[0072] Example 4

[0073] The difference from Example 1 is that the additive was replaced with methyl fluoroacetate, and a positive electrode sheet was finally obtained.

[0074] Example 5

[0075] The difference from Example 1 is that the additive was replaced with ethyl fluoroacetate, and a positive electrode sheet was finally obtained.

[0076] Example 6

[0077] The difference from Example 1 is that the additive was replaced with ethyl perfluorobutyrate, and a positive electrode sheet was finally obtained.

[0078] Example 7

[0079] The difference from Example 1 is that the additive was replaced with ethyl 2,2-difluoropropionate, and a positive electrode sheet was finally obtained.

[0080] Example 8

[0081] The difference from Example 1 is that the mass ratio of lithium iron phosphate, conductive carbon black, PVDF, carbon nanotubes and methyl perfluorooctanoate is 97:0.6:1.8:0.5:0.1, and the positive electrode sheet is finally obtained.

[0082] Example 9

[0083] The difference from Example 1 is that the mass ratio of lithium iron phosphate, conductive carbon black, PVDF, carbon nanotubes and methyl perfluorooctanoate is 97:0.6:1.8:0.5:0.8, and the positive electrode sheet is finally obtained.

[0084] Example 10

[0085] The difference from Example 1 is that the drying temperature is 130°C, resulting in a positive electrode sheet.

[0086] Example 11

[0087] The difference from Example 1 is that the drying temperature is 110°C, resulting in a positive electrode sheet.

[0088] Comparative Example 1

[0089] The difference from Example 1 is that no additives are added, the drying temperature is 150°C, and a positive electrode sheet is finally obtained.

[0090] Comparative Example 2

[0091] The difference from Example 1 is that the additive was replaced with perfluorooctylamine, and a positive electrode sheet was finally obtained.

[0092] Comparative Example 3

[0093] The difference from Example 1 is that the additive was replaced with methyl acetate, and a positive electrode sheet was finally obtained.

[0094] Test method:

[0095] After the positive electrode slurry coating is completed, the positive electrode sheet is taken for weight loss test. At the same time, the remaining positive electrode sheet is rolled to a thickness of 181μm. After rolling, the positive electrode sheet is taken for peel force test.

[0096] Weight loss rate test: Cut 6 pieces of the same size (1.5cm) 2 The small round electrode discs were weighed and recorded. The discs were then placed in an oven and baked at 100℃. Every 15 minutes, the discs were removed and weighed until the weight no longer changed. The weight loss rate was calculated based on the total weight of the discs before and after baking. Weight loss rate = (Weight before baking - Weight after baking) / Weight before baking × 100%.

[0097] Peel force test: The peel force test is conducted using a constant speed tensile testing machine. Samples are cut from the rolled electrode sheet. The width is typically 25±2 mm, and the length is 100 mm. A flat, smooth stainless steel plate is used. A strip of double-sided tape with a width similar to the electrode sheet is adhered to the center of the steel plate. The plate is rolled three times to ensure adhesion without air bubbles. The electrode sheet is then adhered to the double-sided tape, avoiding wrinkles and air bubbles. It is rolled three more times to ensure complete adhesion between the electrode sheet and the tape. The steel plate is fixed to the lower clamp of the tensile testing machine. The free end of the electrode sheet (the unadhesive portion) is clamped in the upper clamp. The testing machine is started, and continuous peeling is performed until the coating is completely separated from the current collector. The system automatically records the peel force-displacement curve.

[0098] The test results are shown in Table 1.

[0099] Table 1

[0100]

[0101] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0102] The addition of additives with the aforementioned general chemical structure to the positive electrode slurry of this application enables the positive electrode sheet to possess the advantages of low NMP residue and high bonding strength. Specifically, the PVDF molecular chain contains a large number of -CF2- segments, and the fluorocarbon chain portion of the aforementioned additives also contains a similar -CF2- structure. Due to the extremely high electronegativity of fluorine atoms, the CF bonds form strong polar bonds, resulting in strong dipole-dipole interactions between the fluorocarbon chains. The binding energy of this fluorine-fluorine interaction is approximately -15 to -27 kJ / mol, and the interaction distance is 0.3 to 0.6 nm, which is sufficient to form stable molecular-level associations in the positive electrode slurry, but insufficient to hinder the volatilization of the additives during baking. This fluorine-fluorine interaction acts as a molecular template in the positive electrode slurry, guiding the PVDF molecular chains to migrate towards the active material-current collector interface. After the additives volatilize during baking, the PVDF retains the favorable orientation induced during baking, forming a stronger bonding network, thereby increasing the electrode sheet peel strength by 40 to 70%. The additive contains ester-based volatile groups, giving it a low boiling point (<165℃). It preferentially volatilizes during the initial baking stage, forming interconnected pore channels, thereby reducing NMP escape resistance. This allows for a 30-50% reduction in NMP residue while maintaining consistent baking process parameters. Even with reduced binder and increased active material content, the electrode peel strength can be improved by 40-70%. Furthermore, the additive achieves residue-free operation and further increases the mass ratio of active material without altering the original electrode formulation, thus improving the cell's energy density. In summary, this application utilizes a lower amount of additive to reduce solvent residue in the positive electrode while improving peel strength, thereby enhancing the battery's energy density and cycle life.

[0103] The above are merely embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A battery cell, comprising a positive electrode, a separator, and a negative electrode, wherein the positive electrode is prepared from a positive electrode slurry, characterized in that, The positive electrode slurry includes positive electrode active material, conductive agent, binder, additive and solvent; The general chemical structural formula of the additive is as follows: Where R1 and R2 are each independently substituted or unsubstituted C1~C1. 18 Alkyl group; and at least one of R1 and R2 is C1~C2. 18 Fluorinated alkyl groups.

2. The battery cell according to claim 1, characterized in that, R1 and R2 are each independently substituted or unsubstituted C1~C 12 Alkyl group; at least one of R1 and R2 is C1~C2. 12 The fluoroalkyl group, wherein the total number of fluorine atoms in R1 and R2 is 1 to 20.

3. The battery cell according to claim 1, characterized in that, The additive is selected from any one or more of methyl perfluorooctanoate, ethyl perfluorobutyrate, ethyl 2,2-difluoropropionate, methyl fluoroacetate, and ethyl fluoroacetate; And / or, based on the dry basis of the positive electrode slurry, the mass percentage of the additive is 0.3~0.5%.

4. The battery cell according to any one of claims 1 to 3, characterized in that, The adhesive includes polyvinylidene fluoride, wherein the number average molecular weight of the polyvinylidene fluoride is 400,000 Da to 600,000 Da.

5. The battery cell according to any one of claims 1 to 3, characterized in that, The mass ratio of the additive to the binder is (0.15~0.3):

1.

6. The battery cell according to any one of claims 1 to 3, characterized in that, The solvent includes N-methylpyrrolidone, and the solid content of the positive electrode slurry is 60-66%.

7. The battery cell according to any one of claims 1 to 3, characterized in that, The positive electrode active material is selected from any one or more of lithium iron phosphate materials, lithium manganese iron phosphate materials, lithium nickel cobalt manganese oxide materials, lithium cobalt oxide, lithium manganese oxide, and lithium-rich manganese-based materials; And / or, the conductive agent is selected from any one or more of conductive carbon black, carbon nanotubes, graphene, natural graphite and artificial graphite; And / or, the mass ratio of the positive electrode active material, the conductive agent, the binder and the additive is (96~97.5):(0.8~1.2):(1.6~2):(0.3~0.5).

8. A method for preparing a battery cell, comprising preparing a positive electrode sheet, and sequentially stacking and assembling the positive electrode sheet, a separator, and a negative electrode sheet to obtain the battery cell, characterized in that, The method for preparing the positive electrode includes: Raw materials including positive electrode active material, conductive agent, binder, additive and solvent are mixed to obtain positive electrode slurry; the positive electrode slurry is coated on the surface of positive electrode current collector and then dried to form positive electrode active layer, to obtain positive electrode sheet; The general chemical structural formula of the additive is as follows: Where R1 and R2 are each independently substituted or unsubstituted C1~C1. 18 Alkyl group; and at least one of R1 and R2 is C1~C2. 18 Fluorinated alkyl groups.

9. The method for preparing a battery cell according to claim 8, characterized in that, The method for preparing the positive electrode sheet further includes: when preparing the positive electrode slurry, a first mixture is made of raw materials including the positive electrode active material, the first conductive agent, the binder and the additive to obtain a first mixture; The raw materials comprising the first mixture and the first solvent are mixed a second time to obtain a second mixture; The raw materials, including the second mixture and the second solvent, are mixed in a third mixture to obtain a third mixture; The raw materials, including the third mixture and the second conductive agent, are mixed in a fourth mixture to obtain the positive electrode slurry.

10. The method for preparing a battery cell according to claim 9, characterized in that, The temperature of the first mixture is 23~27℃, the revolution speed of the first mixture is 15~25rpm, and the mixing time is 30~45min; And / or, the fourth mixing method is dispersion; the revolution speed of the fourth mixing is 20~30 rpm, the dispersion speed of the fourth mixing is 1500~2500 rpm, and the time of the fourth mixing is 60~75 min; And / or, the mass ratio of the first conductive agent to the second conductive agent is 1~2:1; the first conductive agent is selected from any one or more of conductive carbon black, natural graphite and artificial graphite; the second conductive agent is carbon nanotubes and / or graphene.

11. The method for preparing a battery cell according to claim 9, characterized in that, The second mixing method involves kneading, the second mixing speed is 20~30 rpm, and the second mixing time is 60~75 min; And / or, the third mixing method is dispersion, the revolution speed of the third mixing is 20~30 rpm, the dispersion speed of the third mixing is 1500~2500 rpm, and the time of the third mixing is 90~120 min; And / or, the mass of the first solvent is 80-90% of the total mass of the first solvent and the second solvent.

12. The method for preparing a battery cell according to any one of claims 8 to 11, characterized in that, The drying temperature is 120~130℃; and / or, the double-sided areal density of the positive electrode sheet is 400~430 g / m³. 2 .

13. A battery device, characterized in that, The battery device includes the battery cell according to any one of claims 1 to 7, and the battery device includes any one or more of the following: battery module, battery pack, and energy storage battery.

14. An electrical appliance, characterized in that, The electrical device includes the battery device of claim 13, the battery device being used to provide electrical energy.

15. An energy storage device, characterized in that, The energy storage device includes the battery device of claim 13, the battery device being used to store electrical energy.